Governance, Capital Structure, and Company Performance of Property and Real Estate Companies - Tasman, Abel; Oktari, Indria; Lukman, Syukri (CV. ITTC INDONESIA, 2025)
This research examines the influence of board size, audit committee, female directorship, and capital structure on company performance for property and real estate sector companies listed on the Indonesia Stock Exchange. Meanwhile, the sample in this research was determined using a purposive sampling method, namely property and real estate sector companies for five consecutive years from 2019-2023, resulting in a total sample of 44 companies with 220 observation data. The data analysis method uses panel data regression. The research results show that board size has a significant positive effect on company performance. The audit committee has an insignificant negative impact on company performance. Female direct rosehip has a significant positive effect on company performance. Capital structure has an insignificant negative impact on company performance. Simultaneously the variables of board size, audit committee, female directorship, and capital structure have a significant effect on company performance.